Ward Climate in a High-Secure Forensic Psychiatric Setting: Comparing Two Instruments. Issue 3 (3rd July 2018) - de Vries, Meike Godelieve; Brazil, Inti Angelo; van der Helm, Peer; Verkes, Robbert-Jan; Bulten, Berend Hendrik
Abstract: The psychometric properties and associations between the Essen Climate Evaluation Schema (EssenCES) and the Group Climate Instrument-revised (GCI-r) were examined. These self-report questionnaires assessing ward climate were filled out by 123 male patients, residing in 3 high-secure forensic psychiatric facilities. Good internal consistency was found for all subscales of both instruments. The original factor structure was confirmed for the EssenCES, but not for the GCI-r. Bivariate correlation analyses indicated that the instruments measure related concepts. The results of this study call for further development and validation and for finding common grounds in the definition and operationalization of ward climate.